2017
DOI: 10.1021/acs.jpcc.7b01278
|View full text |Cite
|
Sign up to set email alerts
|

Bioimmobilization Matrices with Ultrahigh Efficiency Based on Combined Polymerizations of Chemical Oxidation and Metal Organic Coordination for Biosensing

Abstract: Facile regulation and enhancing of the performance of bioimmobilization materials is a key factor for their applications for biosensing, biocatalysis, bioreactor, and so on. Here, we propose a method of combined polymerizations of chemical oxidation and metal organic coordination to develop enhanced bioimmobilization matrices for high performance biosensing. Being different from conventional methods that are based on sole polymerization, the new method elaborated chemical oxidation to one-pot obtain oligomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…[5][6][7] Up to now, various techniques have been employed for the simultaneous determination of HQ, RC and CC, including chromatography, 8 spectrophotometry, 9 synchronous fluorescence 10 and electrochemistry. [11][12][13][14][15][16][17][18] Among them, the electrochemical technique is the more efficient method in the simultaneous determination of dihydroxybenzene isomers due to its excellent properties such as simple operation, high sensitivity and low cost. Although dihydroxybenzene isomers are electrochemically active, it was found that the oxidation potentials of CC and HQ on bare electrode were close to each other.…”
mentioning
confidence: 99%
“…[5][6][7] Up to now, various techniques have been employed for the simultaneous determination of HQ, RC and CC, including chromatography, 8 spectrophotometry, 9 synchronous fluorescence 10 and electrochemistry. [11][12][13][14][15][16][17][18] Among them, the electrochemical technique is the more efficient method in the simultaneous determination of dihydroxybenzene isomers due to its excellent properties such as simple operation, high sensitivity and low cost. Although dihydroxybenzene isomers are electrochemically active, it was found that the oxidation potentials of CC and HQ on bare electrode were close to each other.…”
mentioning
confidence: 99%